Anarkisme Demonstrasi Mahasiswa: Studi Kasus Pada Universitas Islam Negeri Alauddin Makassar - Hasse J. (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2012)
This study aims to describe the phenomenon of violence in the student demonstrations in Makassar. Violence in the demonstrations, especially by students at several universities in Makassar is a sight familiar to the public. Submission of student aspirations through a demonstration is considered a very effective medium. However, the demonstration is always ended with a riot / violence. Metod collection of data through observation of student development activities, demonstration activities, both inside and outside the college; in-depth interviews conducted on-campus students and stakeholders and the public; conducted group discussions with students who are involved or not in any demonstration; study documentation/literature do specifically to research and writing as well as opinion pieces in newspapers that are stored in several parties.